Prioritization of Service Quality Influences on Patients` Satisfaction using Analytic Hierarchy Process: the Nigeria Experience - Bilqis Bolanle AMOLE; Emmanuel Olateju OYATOYE; Sulaimon Olanrewaju ADEBIYI (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2015)
This paper proposed the use of Analytic Hierarchy Process (AHP) for the prioritization of factors influencing patients’ satisfaction with service quality dimensions of public teaching hospitals in Southwest Nigeria. To accomplish this purpose, data were collected from 326 respondents who were patients of public teaching hospitals in southwest Nigeria. The data were modeled and analysed with AHP excel software. The results show the rank of service quality dimensions criteria and the alternatives based on the respondents preferences for satisfaction. The finding revealed that empathy dimension criteria were given the highest preference while the waiting time dimension was the least preferred. In the global ranking of all the decision alternatives of the service quality dimensions of hospitals, the interaction of patients with hospital staff were given highest preference while the least preferred were the unpredictable time for treatment. This study recommends that there is need for healthcare managers to consider the perception of patients towards service quality dimensions alternatives on how they ranked those factors so as to improve their quality of service that would enhance patient satisfaction.